Comparative Study of Disaster Regulations in Analyzing Vulnerability Level of Elementary School Building Structures in Yogyakarta - Lilis Tiyani; Hakas Prayuda; Bagus Soebandono (Department of Civil Engineering, Faculty of Engineering, Universitas Brawijaya, 2022)
This research was conducted to compare several regulations that evaluate the level of vulnerability of school buildings in Yogyakarta. The regulations used in this study are a guide to assessing and repairing damage to public housing buildings due to the earthquake according to the Department of Public Works in 2000, technical guidelines for safe school rehabilitation according to the National Disaster Management Agency in 2011, a broken one or two-story simple building block safety check guide due to the earthquake according to the 2009 World Seismic Safety Initiative and using rapid visual screening of building for potential seismic hazards according to the Federal Emergency Management Agency No. 154 of 2002. The 25 schools selected in this study were located in areas prone to earthquakes, volcanoes erupted and prone to landslides. Through this research, the results of the appropriate regulations were obtained to evaluate the rapid level of vulnerability of buildings to disasters and evaluation of certain disaster cases was needed because the regulations did not accommodate all types of disasters.